Efficient removal of low concentration methyl mercaptan by HKUST-1 membrane constructed on porous alumina granules. Issue 4 (12th January 2018) - Ma, Xiang; Peng, Shengpan; Li, Weiman; Liu, Haidi; Chen, Yunfa
Abstract : A HKUST-1 metal–organic framework membrane was constructed on porous Al2 O3 granules for the first time for the removal of low concentration CH3 SH. Abstract : A HKUST-1 metal–organic framework membrane was constructed on porous Al2 O3 granules for the first time for the removal of low concentration CH3 SH. The granules exhibited higher sulfur capacity than the pure HKUST-1 powders owing to the excellent dispersion of the MOF membrane on the Al2 O3 substrate. The granules also showed good water resistibility.